2013
DOI: 10.1039/c3pp25425a
|View full text |Cite
|
Sign up to set email alerts
|

Photodynamic therapy for hilar bile duct cancer: clinical evidence for improved tumoricidal tissue penetration by temoporfin

Abstract: Photodynamic therapy (PDT) has been established for palliation of non-resectable hilar bile duct cancer (hBDC). Ablation of hBDC using porfimer (P-PDT) improves cholestasis and survival. However, the tumoricidal effect is confined to the inner 4 mm of the tumor wall. Here, we have studied whether temoporfin PDT (T-PDT) shows an efficient local response and an increased tumoricidal penetration depth. In the first stage of a phase-II trial (NCT01016002), eleven patients with hBDC (Bismuth III-IV) were treated wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
25
1
6

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(32 citation statements)
references
References 49 publications
0
25
1
6
Order By: Relevance
“…14 In a study, 11 patients with hilar cholangiocarcinoma (Bismuth III-IV) were treated with temoporfin PDT and stenting and 10 could be analyzed for local tumor response. 15 Tumoricidal efficacy was 90%; 4 patients showed tumoricidal depth of greater than or equal to 7.5; and cholestasis and palliation improved in 8 patients with an overall median survival of 18 months after the first PDT. 15 In another study, combined stenting and PDT performed with a low Foscan dose resulted in equal and potentially longer survival times compared with standard Photofrin PDT and lowered the risk of side effects strongly.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…14 In a study, 11 patients with hilar cholangiocarcinoma (Bismuth III-IV) were treated with temoporfin PDT and stenting and 10 could be analyzed for local tumor response. 15 Tumoricidal efficacy was 90%; 4 patients showed tumoricidal depth of greater than or equal to 7.5; and cholestasis and palliation improved in 8 patients with an overall median survival of 18 months after the first PDT. 15 In another study, combined stenting and PDT performed with a low Foscan dose resulted in equal and potentially longer survival times compared with standard Photofrin PDT and lowered the risk of side effects strongly.…”
Section: Discussionmentioning
confidence: 97%
“…15 Tumoricidal efficacy was 90%; 4 patients showed tumoricidal depth of greater than or equal to 7.5; and cholestasis and palliation improved in 8 patients with an overall median survival of 18 months after the first PDT. 15 In another study, combined stenting and PDT performed with a low Foscan dose resulted in equal and potentially longer survival times compared with standard Photofrin PDT and lowered the risk of side effects strongly. 16 Unfortunately, those drugs are not FDA approved in the United States.…”
Section: Discussionmentioning
confidence: 97%
“…A recent trial used Foscan at a regular (high) dose regime and resulted in good efficiency and deeper tissue necrosis as observed with porfimer sodium PDT, but a similar side effect profile 6 . An earlier study reported good treatment effects, but also a significant risk of complications 7 .…”
Section: Introductionmentioning
confidence: 90%
“…It was decided to apply 3 mg of Foscan -approx. a quarter of the standard dose -and to increase the irradiation to 50-100 J/cm from 30 J/cm used in the high drug dose regime 6 . The DLI was initially chosen to 20 hours, but later increased to > 67 hours due to the results of pharmacokinetic measurements.…”
Section: Introductionmentioning
confidence: 99%
“…The classes of PDT drugs include porphyrin derivatives, chlorins, phthalocyanines, and porphycenes [69,92,98]. Some clinical attempts to improve treatment of cancers and infectious diseases by PDT include non-respectable hilar bile duct cancer (drug used temoprfin) [99], oral cancer (photofrin, liposomal aluminum-cholride phthalocyanine) [100], pain determination in patients (red light/5-aminolevulinic acid) [93,101,102]. Readers are also referred to a recent review by Mamalis et al for the laser and light treatments of keloids [103].…”
Section: Photodynamic Drug-liposome Formulationsmentioning
confidence: 99%